Program English Training Teachers (ETT) Bagi Guru-Guru SMPIT IQRA Kota Bengkulu - agung suhadi; Ivan Achmad Nurcholis; Kiagus Baluqiah (PRAWARA Jurnal ABDIMAS, 2023)
- English plays a very crucial role, especially for education aspect. Teachers are further required for having good skills in English communication both in learning with their students and also other people. It is hoped that the ability to communicate in English will open up opportunities for teachers, students and schools to have careers, national landscapes, as well as dig up information both at the global and international levels. Seeing the importance of using the ability to communicate in English, the community service team from the English Language Education Study Program at the University of Muhammadiyah Bengkulu provided training (workshop) for teachers at IT IQRA Middle School, Bengkulu City. This activity provides provision, knowledge and training for teachers so that they are proficient in speaking English. The methods used in this training include material assistance (lectures), discussions; question and answer, and practice speaking English. Prior to the training, a pretest was given to see the initial ability of the teachers to master spoken English. Then they were given training and carried out a post test to see the results of their participation in the English speaking training. From the results of the activities of the IT IQRA Middle School teachers, it can be interpreted that in general the training activities provided positive results, namely growing the enthusiasm and interest of teachers to use English in their daily activities while at school. In the aspect of communication skills, some teachers are already very skilled in speaking and this ability makes other teachers become brave and speak English more often. It is hoped that this training activity can be followed up considering how motivated the teachers are through a sustainable program that can be carried out through a broader cooperation program.